A comparison between bio-mos and palm kernel expeller as mannan-oligosacharids sources on the ileal microbial population in broiler chickens - B., Navidshad; Jahromi, Mohammad Faseleh; Liang, Juan Boo (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A total of 60 1-d-old male broiler chicks (Cobb 500) in a finisher period (29-42d) were allotted to 3 dietary treatments namely a control diet, a diet with 20 g/kg Bio-Mos, and a diet containing 200 g/kg of an enzymatically-treated PKE. There were no differences in the ileal population of Lactobacillus and Enterococcus or Enterobacteriaceae among the experimental groups. But, birds fed diets containing PKE or Bio-oOs had a lower population of Escherichia coli than the control group. The results showed that PKE potentially has comparable prebiotic features as commercial Bio-Mos for poultry.